Plan de negocio para la creación de un laboratorio de dosimetría personal dirigido al personal ocupacional expuesto a radiación en instituciones médicas públicas y privadas de Quito-Ecuador - García Castillo, Ana Camila (2019)
In the medical area, there are fields of radiology and radiotherapy, in which the tests carried out require the use of machinery that emits ionizing radiation, a type of radiation that is harmful to humans. Ecuador has regulations that safeguard the patient's health in the face of this type of radiation, however, there is not the same care for the affected physicians. For this reason, there is a social tendency towards greater care for the cancerous and reproductive health of the occupational personnel exposed to radiation. Ecuador currently has a single laboratory dedicated to providing the Personal Dosimetry Services, which belongs to the Undersecretariat of Control and Nuclear Applications. Through market research, the business plan identified a high demand for the service, as well as the needs that were not being covered by the current laboratory. Thus, the elements of value for the client and user were defined through the matrix of the four actions. The business idea will provide a safe and high-quality service, through innovative technology acquired locally and internationally, highly trained personnel with years of experience in the area and appropriate and proven processes. Additionally, it will implement new payment mechanisms, a complementary way for doses shipment, training by area, and clear, easy-to-understand information that is user-friendly. Finally, it is important to point out that, through an initial investment of 290,275.00 dollars, the laboratory is to be started up. However, the business idea turns out to be not profitable in the short term due to the high import and personnel costs, costs that the current laboratory does not consider since they are subsidized by the State. For this reason, entering the industry through the delivery of the Personal Dosimetry Service requires a high level of capital, commitment on the part of the laboratory managers and patience to be able to see long-term results and be competitive.